Hot money - Francis, Dick. (New York : Putnam, 1988)
Ian perseveres in his search into the past; discovering the hate that builds silently through the years, the terrible price the relatives pay for their fathers' sins, and a twisted knot of passion compelled to turn love to punishment.
Booklist.
Young Adult.
Young Adult
Keywords: Horse racing -- Fiction; Jockeys -- Fiction; Detective and mystery stories